INTERPRETATION OF TERM “INTERESTS” IN CRIMINAL LAW - Baumanis, Jānis (Administrative and Criminal Justice, 2015)
The interest is the basis, the driver, the initiator, the subject and the object for emergence, development and existence of criminal law. While analyzing the interpretation of the term “interest” the author concludes that despite the association of the interest with psychological processes, in the legal doctrine of criminal law “the interest” most frequently analyses not the mental attitude of an individual, but instead – the impartial aspects of the criminal offence within the framework of the object of such offence. In the contemporary criminal law, the interests as the object of a criminal offence are a value, which is protected by the potentiality of criminal punishment.